2004
DOI: 10.1084/jem.20031666
|View full text |Cite
|
Sign up to set email alerts
|

Uteroglobin Represses Allergen-induced Inflammatory Response by Blocking PGD2 Receptor–mediated Functions

Abstract: Uteroglobin (UG) is an antiinflammatory protein secreted by the epithelial lining of all organs communicating with the external environment. We reported previously that UG-knockout mice manifest exaggerated inflammatory response to allergen, characterized by increased eotaxin and Th2 cytokine gene expression, and eosinophil infiltration in the lungs. In this study, we uncovered that the airway epithelia of these mice also express high levels of cyclooxygenase (COX)-2, a key enzyme for the production of proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 51 publications
3
93
1
Order By: Relevance
“…We previously reported that the lungs of the UG-KO mice express genes that are known to mediate inflammation (17). In the present study, we found that the expression of several other genes related to inflammation (e.g.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We previously reported that the lungs of the UG-KO mice express genes that are known to mediate inflammation (17). In the present study, we found that the expression of several other genes related to inflammation (e.g.…”
Section: Discussionsupporting
confidence: 65%
“…UG-KO Mouse Lungs Express High Levels of S100A8 and S100A9-We previously reported that UG-KO mice are susceptible to pulmonary inflammation (17), and recently it has been demonstrated that RAGE and its ligands may constitute a FIGURE 2. Expression of S100A8 and S100A9 in WT and UG-KO mice and expression of RAGE in B16F10 cells.…”
Section: Elevated Levels Of Metastasis In the Lungs Of Mice Lacking Umentioning
confidence: 99%
See 1 more Smart Citation
“…CC-10 appeared to have a high homology with rabbit uteroglobin, which has immunosuppressive, anti-inflammatory, anti-proteinase, and anti-phospholipase A2 properties (20)(21)(22)(23)(24). Therefore, CC-10 might play an important role in antiinflammatory response which is a critical factor for immune modulation in cancer prevention and treatment and CC-10 may used for a new marker indicating the severity of various inflammatory lung diseases (34).…”
Section: Discussionmentioning
confidence: 99%
“…CC-10 is the founding member of a growing superfamily of proteins called secretoglobin (Scgb) (19). Numerous studies have demonstrated that CC-10 is a multifunctional protein with anti-inflammatory (20) and immunomodulatory properties (21). It inhibits soluble phospholipase A2 activity (22), binds and perhaps sequesters hydrophobic ligands such as progesterone, retinols, polychlorinated biphenyls, phospholipids and prostaglandins.…”
Section: Introductionmentioning
confidence: 99%